Effects of different storage conditions on mechanical properties of CAD/CAM restorative materials = Efecto de diferentes condiciones de almacenamiento en las propiedades mecánicas de materiales restauradores CAD/CAM - Atay, Ayşe
The aim of this study was to evaluate mechanical properties of six new-generation all-ceramic materials for CAD/CAM (Lava Ultimate [LU], VITA Mark II [VM], InCoris TZI [IC], IPS e.max CAD [EM], VITA Suprinity [VS], IPS Empress CAD [EC]) and two different provisional restoration CAD/CAM materials (Telio CAD [TC], Vita CAD-Temp [VC]) after different storage conditions. 36 bar-shaped samples of 4 mm in width and 14 mm in length with 1.2 mm thicknesses were prepared from each material group (N=288). The specimens from each material were kept under three different storage conditions (n=12): under dry conditions at room temperature; 37°C distilled water for 7 days; and 37°C distilled water for 7 days followed by 10,000 thermal cycles. All specimens were subjected to a 3-point flexural test with a crosshead speed of 1.0 mm/min. The specimens were loaded until failure. Twelve fractured specimens after the flexural test from each group were used for the Vickers hardness test (under 300 gf of loading in 15 seconds). The flexural modulus, flexural strength and Vickers hardness values were separately analyzed with two-way analysis of variance, Tukey's multiple comparison tests at a significance level of p<0.05. There were statistically significant differences between materials and storage conditions according to flexural modulus, flexural strength and Vickers hardness values (p<0.05). The flexural strength, flexural modulus and Vickers hardness values of LU, VC, TC, VS and IC decreased after water storage followed by thermal cycling (p<0.05). The mechanical properties of provisional restoration CAD/CAM materials had showed a significantly decrease after water storage followed by thermal cycles but their mechanical properties were acceptable for fabrication of provisional restorations. The mechanical properties of VM, EC and EM were not affected by different storage conditions whereas IC and VS were affected.